Inclusion complexes of tea polyphenols with HP‐β‐cyclodextrin:Preparation, characterization, molecular docking, and antioxidant activity. Issue 4 (16th March 2020) - Zhong, Yuanyuan; Li, Wenhui; Ran, Lidan; Hou, Ran; Han, Ping; Lu, Shiling; Wang, Qingling; Zhao, Wei; Zhu, Yi; Dong, Juan
Abstract : Abstract: The purpose of this study was to prepare and characterize inclusion complexes between tea polyphenol (TP) and hydroxypropyl‐β‐cyclodextrin (HP‐β‐CD), and to evaluate their antioxidant properties. Freeze‐drying was used to prepare the inclusion complex of TP/HP‐β‐CD at different component ratios (1:0.5, 1:1, and 1:2). The supermolecular structure of the TP/HP‐β‐CD complex was characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). Molecular docking was used to simulate the positions and interactions of the binding sites of TP/HP‐β‐CD inclusion complexes and target protein receptors. In addition, the effects of TP/HP‐β‐CD inclusion complexes on myofibrillar protein (MP) from lamb tripe were observed under oxidative conditions. Results showed that TP was encapsulated in the cavity of HP‐β‐CD to form an optimal complex with 1:2 molar ratio of stoichiometry, while the FTIR, TGA, and SEM studies also support the inclusion process. Molecular modeling results were systematically analyzed to determine the stability of inclusion complexes and protein. Furthermore, the addition of an appropriate concentration (5 to 105 µmol/g) of TP/HP‐β‐CD inclusion complex decreased the carbonyl content, hydrophobicity, and protein aggregation of MP from lamb tripe, whereas it increased the sulfhydryl content. This improved antioxidant activity and bioavailability of the inclusion complexes will be beneficial for its potential applications in food. Practical Application: Tea polyphenol was an antioxidant with potential for the field of food. In this study, the unstable properties of tea polyphenols were evaluated and were improved by inclusion of HP‐β‐cyclodextrin. The binding mode of the inclusion complex with protein was revealed via the molecular docking method, and the application of inclusion complex to control protein oxidation was studied. Results showed that the inclusion complex could effectively inhibit protein oxidation, which can provide a reference for the application of polyphenols in meat products and the improvement of protein properties.